International Humanitarian Law: Alleviating Human Suffering During Armed Conflicts - Chalisey, Krishna Chandra (NCWA Annual Journal, 2026)
International Humanitarian Law (IHL) comprises a body of rules designed to reduce the humanitarian impact of armed conflicts. It is also known as the law of armed conflict or the law of war. In situations of armed conflict, the International Committee of the Red Cross (ICRC) serves as the guardian and custodian of IHL. The core legal foundations of IHL are the four Geneva Conventions of 1949 and their Additional Protocols of 1977. The ICRC works in cooperation with sovereign States, United Nations organs, and other relevant institutions to promote compliance with IHL during armed conflicts. For humanitarian purposes, IHL seeks, in times of armed conflict, to protect individuals who are not, or are no longer, directly participating in hostilities, while also limiting the means and methods of warfare. This article aims to identify the major challenges facing IHL and related issues worldwide. It also examines the state of IHL in Nepal and proposes possible measures that may be adopted to strengthen its application. Considerable efforts remain necessary to ensure respect for IHL, particularly through enhanced compliance mechanisms and enforcement. IHL is of particular relevance to Nepal in light of the decade-long insurgency between the state and the former Communist Party of Nepal (Maoist), as the victims of the conflict have been awaiting justice for nearly two decades. There is a significant gap in the implementation of IHL measures, as well as a limited level of treaty participation in the field of IHL. Accordingly, the government needs to address both the strengthening of domestic implementation measures and the expansion of treaty participation.